Production of Biodiesel From Croton gratissimus Oil Using Sulfated Zirconia and KOH as Catalysts - Jiyane, Phiwe Charles; Tumba, Kaniki; Musonge, Paul (Frontiers in Energy Research, 2021)
Optimization studies for the esterification and transesterification of oil extracted from Croton gratissimus grains were carried out using the response surface methodology (RMS) that utilizes the central composite design (CCD) and the analysis of variance (ANOVA). A 23 full-factorial rotatable CCD for three independent variables at five levels was developed in each case, giving a total of 20 experiments needed per study. The three design factors chosen for study were the catalyst concentration, methanol-to-oil ratio, and the reaction temperature. The values of the acid value of oil (in esterification) and the percentage FAME yield and FAME purity (in transesterification) were taken as the responses of the designed experiments. In the optimization of the esterification and transesterification processes, the ANOVA showed that both quadratic regression models developed were significant. The optimum operating conditions for the esterification process that could give an optimum acid value of 2.693 mg KOH/g of oil were found to be 10.96 mass% SO42–/ZrO2 catalyst concentration, 27.60 methanol-to-oil ratio, and 64°C reaction temperature. In the optimization of the transesterification process, the model revealed that the catalyst concentration and the methanol-to-oil ratio were the terms that had the most influence on the % FAME yield and the % FAME purity of the final biodiesel product. From the combined regression model, it was established that optimum responses of the 84.51% FAME yield and 90.66% FAME purity could be achieved when operating the transesterification process at 1.439 mass% KOH catalyst concentration, 7.472 methanol-to-oil ratio, and at a temperature of 63.50°C. Furthermore, in the two-step biodiesel synthesis, a predominantly monoclinic-phased sulfated zirconia (SO42–/ZrO2) catalyst exhibited high activity in the esterification of high free fatty acid oil extracted from Croton gratissimus grains. A 91% reduction in the acid value of the Croton gratissimus oil from 21.46 mg KOH/g of oil to 2.006 mg KOH/g of oil, well below the 4 mg KOH/g of oil maximum limit, was achieved. This resulted in the high FAME yield and purity of the biodiesel produced in the subsequent catalytic transesterification of oil using KOH.